2021
DOI: 10.3390/app112210871
|View full text |Cite
|
Sign up to set email alerts
|

Building and Evaluating an Annotated Corpus for Automated Recognition of Chat-Based Social Engineering Attacks

Abstract: Chat-based Social Engineering (CSE) is widely recognized as a key factor to successful cyber-attacks, especially in small and medium-sized enterprise (SME) environments. Despite the interest in preventing CSE attacks, few studies have considered the specific features of the language used by the attackers. This work contributes to the area of early-stage automated CSE attack recognition by proposing an approach for building and annotating a specific-purpose corpus and presenting its application in the CSE domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…To achieve her goal, a malicious interlocutor repeats her arguments many times in a conversation to convince and manipulate her partner. This was also confirmed, after processing our CSE corpus [2], where we observed that 83% of social engineering attackers tend to insist on their arguments to exfiltrate the targeted type of critical information. The persistence of an interlocutor to regurgitate the same topic that could lead to sensitive data exfiltration can be considered an enabler of a successful CSE attack.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…To achieve her goal, a malicious interlocutor repeats her arguments many times in a conversation to convince and manipulate her partner. This was also confirmed, after processing our CSE corpus [2], where we observed that 83% of social engineering attackers tend to insist on their arguments to exfiltrate the targeted type of critical information. The persistence of an interlocutor to regurgitate the same topic that could lead to sensitive data exfiltration can be considered an enabler of a successful CSE attack.…”
Section: Introductionsupporting
confidence: 80%
“…This approach results in our proposed model, called CSE-PersistenceBERT, which learns a universal representation that transfers knowledge with only minimal adaptation to the paraphrase recognition task. Initially, the CSE-PersistenceBERT model has access to a large corpus of unlabeled text on which BERT has been pre-trained, and later it uses the CSE-Persistence corpus, which emerged from the CSE corpus of our previous work [2]. CSE-Persistence corpus generated after manually annotating the CSE corpus and utilizing the CSE ontology [2].…”
Section: Introductionmentioning
confidence: 99%
“…After conducting a quantitative analysis to examine the existing persuasion principles in our CSE corpus [41], we concluded that authority and commitment were the most common persuasion principles used by social engineers. Nevertheless, in this study, all persuasion principles were considered to be equally important.…”
Section: B Cialdini's Persuasion Principlesmentioning
confidence: 99%
“…Thus, identifying a persuasive payload in a sentence means identifying informative local features that may be repeated, regardless of where they are placed in the sentence. Let us consider the following sentence that is part of our CSE Corpus [41]: "I need that information to report back to my boss.". We can easily conclude that some of the words are highly informative of a persuasive payload existence (i.e., the word boss denotes a possible use of the persuasion principle of authority), which holds true regardless of the position of this word in the sentence.…”
Section: The Proposed Cse-pucmentioning
confidence: 99%
“…Koyun & Al Janabi (2017) [12] Aldawood & Skinner (2019) [13] Many studies focused on natural language processing (NLP) to detect potential SEAs. [14] proposed a chat-based SEA recognition by evaluation of specific purpose written text on social engineering domain. The study enhanced the understanding of in-context features used by attackers.…”
Section: Internationalmentioning
confidence: 99%